Heptapleurum kemirianum (Araliaceae), a new subalpine endemic shrub from Gayo Plateau, Sumatra - Mustaqim, Wendy A.; Arico, Zulfan; Misdi; Hutabarat, Prima W.k. (Phytotaxa, 2026)
Heptapleurum kemirianum Frodin ex Mustaqim & Hutabarat is described. The species is known from five specimens collected from the subalpine vegetation of the Gayo Plateau, northern Sumatra. This species is most closely related to Heptapleurum rugosum (Blume) Boerl. and Heptapleurum wrayi King because the flowers are arranged racemosely on the ultimate branches of the inflorescences. The new species differs from H. rugosum in having smaller, thickly coriaceous leaflets with a shining upper surface, and much shorter inflorescences, while differs from H. wrayi in having fewer leaflets, thicker leaflets with a shiny upper surface and strongly revolute margin, as well as much shorter inflorescences. Detailed morphological descriptions, photographs, and discussions are provided.